LEXICAL BORROWING ANALYSIS OF JAVA ISLAND CITY AND REGION’S NAME ON THE立地成 (LÌDÌ CHÉNG) SITE - Laurenctius Jefferson Natan (UIBU, 2023)
In the development of a language, there are transformation. One of the transformation caused by loanwords which a language insert the lexicon or vocabulary from other language. According to Octaviana (2021), the loanwords or borrowing is one of categorization of communication strategies in the language. This research is about loanwords analysis of Java Island’s city and region names on the立地成 (lìdì chéng) site and aims to identify the language loanwords classification by Niklas-Salminen theory. Through this research, the Java Island’s name of city and region on the立地成 (lìdì chéng) site were analyzed to know the loanwords classification to Chinese. From this research result, it was found that 24 names of city and region absorbed phonological, 35 names of city and region absorbed morphosyntactic, 32 names of city and region absorbed lexical, 2 names of city and region absorbed xenism, and 6 names city and region absorbed xenism-morphosyntactic. Therefore, this research is needed to analyze the absorption of Java Island’s city and region names into Chinese so that knowing by peoples.